Criterion validity and reliability of an instrumented mouthguard under pendulum impactor conditions - Austin, K.; Nicholas, K. J.; Jones, C. M.; Loosemore, M. (Sports Engineering, 2023)
The popularity of instrumented mouthguards (iMGs) use to measure head impact kinematics in contact sports is growing. To accurately compare between systems, mouthguards should be subjected to standardised laboratory validation testing. The study aimed to establish the validity and reliability of a mouthguard system under independently collected pendulum impactor conditions. A NOCSAE anthropometric testing device with attached mouthguard was impacted in four different locations (front, front boss, rear, rear boss) at four target linear accelerations (25, 50, 75 and 100 g) with two different impactor caps (padded and rigid). Peak linear acceleration, peak rotational velocity and peak rotational acceleration values from the mouthguard were compared against the reference data with a battery of statistical tests, namely R squared values, Lin`s concordance correlation coefficient, intraclass correlation coefficients and Bland Altman analysis. Results indicate the iMG produces valid and reliable data comparable to that of the anthropomorphic testing device reference, with all measured variables reported `excellent` intraclass correlation coefficients above 0.95; concordance correlation coefficients above 0.95; minimal average bias with Bland Altman analysis and R squared values above 0.92 for all measured variables. Results indicate the iMG is appropriately valid and reliable enough to next establish on-field validity.